2012
DOI: 10.3329/jbau.v9i2.10989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship and similarity of some selected chicken strains

Abstract: Random amplified polymorphism DNA (RAPD) technique was applied to detect genetic similarity between seven local  chicken strains selected for eggs and meat production in Bangladesh. Conservation and improvement strategies     ought to be based on proper genetic characterization in association with phenotypic characterization. White Leghorn, White Rock, Rhode Island Red, and Barred Plymouth Rock fall under recognized strain and Hilly, Deshi and Necked Neck fall under native bird group. Based on four oligonucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…This value indicated that these two types of hilly chickens have a minimum genetic differentiation. A similar finding was reported by Tadano et al (2007) for native Japanese poultry breeds and in contrast with lower genetic differentiation values found in 8 Finnish chicken breeds by Vanhala et al (1998) and Monira et al (2011) of a Bangladesh study. The genetic diversity of the two hilly types was also assessed by calculating the polymorphic information content (PIC) values.…”
Section: Breed Variability and Differentiationsupporting
confidence: 87%
“…This value indicated that these two types of hilly chickens have a minimum genetic differentiation. A similar finding was reported by Tadano et al (2007) for native Japanese poultry breeds and in contrast with lower genetic differentiation values found in 8 Finnish chicken breeds by Vanhala et al (1998) and Monira et al (2011) of a Bangladesh study. The genetic diversity of the two hilly types was also assessed by calculating the polymorphic information content (PIC) values.…”
Section: Breed Variability and Differentiationsupporting
confidence: 87%
“…In an independent studies in different locations and different breeds using RAPD phylogenetic relationship and diversity were established by some authors in chickens (Monira et al, 2011;Yap and Kumaran, 2011;Tamara et al, 2012;Alatafi et al, 2013), in ducks (Alyethodi et al, 2010) and in rabbit breeds (ElBayomi et al, 2013). Random and microsatellite markers were used to detect the genetic lineage and to determinate T genetic variation in chicken (Olowofeso et al, 2005;Tadano et al, 2013).…”
mentioning
confidence: 99%
“…This result indicates that weights at sexual maturity are very important on body weight on subsequent periods. 16 week age (WT 2 ) K g. Body weight at20 weeks age (WT 3 ) K g. Body weight at 24 week age (WT 4 ) K g .…”
Section: Results and Discutionmentioning
confidence: 99%